The BFG - Dahl, Roald (Puffin, 2016)
Kidsnatched from her orphange by a BFG (Big Friendly Giant), who spends his life blowing happy dreams to children, Sophie concocts with him a plan to save the world from nine other man-gobbling cannybull giants.